Peculiarities of interaction of sphere of consciousness and subconsciousness in terms of motor mnemic activity of teacher-musician - Husak, V.A. (Pedagogy of Higher and Secondary Education, 2009)
The article deals with the problem of peculiarities of interaction of consciousness and subconsciousness spheres in functioning locomotor memory of studenis-playrrs in the processes of training playing technics and public playing.